Assessment of the contribution of municipal solid waste dumping coupled with open burning to the contamination of the surrounding environment by plasticizers - Rejeb, Oumaima; Afsa, Sabrine; Toumi, Dhekra; Rando, Rossana; Hassani, Rym; Harzallah-Skhiri, Fethia; Ben Mansour, Hedi; Bella, Giuseppa Di (Waste management (Elmsford), 2025)
•MSW open-dump site represents a hotspot for a combined environmental pollution.•GC–MS/MS was used to quantify PAE and NPP in the dump site and surrounding area.•Plasticizers can accumulate in plants and contaminate the food chain.•Fly ash contributes to the spread of plasticizers via atmospheric transport.•MSW mismanagement may pose a serious environmental and human health risk. Open dumping sites have become a hotspot for combined environmental pollution. In developing countries, including Tunisia, this practice is commonly coupled with municipal solid waste open burning as a costless method compared to other methodologies. However, the resulting pollution may cause a significant hazard to the surrounding environment and the nearby population’s health by spreading dangerous chemicals such as plasticizers. In this context, the current study aimed at evaluating the levels of contamination across the dumpsite coupled with open burnings in Mahdia city by plasticizers. Gas chromatography-single quadrupole mass spectrometry analyses were conducted to identify and measure the concentration levels of 18 plasticizers in various environmental matrices. The results of this study have shown the occurrence of several plasticizers (n = 10) at a wide range of concentrations, with di(2-ethylhexyl) phthalate, diisobutyl phthalate, and di(2-ethylhexyl) terephthalate being the predominant compounds. Interestingly, the total concentration of plasticizers detected in plant matrices was significantly higher than those found in the majority of the remaining matrices. Namely, the detected concentrations of total plasticizers were in the following order: plant samples (3.777 mg Kg−1 dw) > fly ash (2.581 mg Kg−1 dw) > soil-leachate (1.403 mg Kg−1 dw) > soil (0.816 mg Kg−1 dw) > sediment (0.505 mg Kg−1 dw) > water (0.009 mg L-1 dw). Our findings confirm a large distribution of phthalates (PAE) and non-phthalates (NPP) across the open dumping site in “Sabkha of Oued EL Maleh.” The detection of plasticizers in plant materials affirms their potential to bioconcentrate through the food chain. Atmospheric transport and deposition of pollutants following waste-burning practices could play a significant role in the contamination of the neighboring area, highlighting a serious environmental and health impact of MSW mismanagement.